Deconstructive Variations: Music and Reason in Western Society - Subotnik, Rose Rosengard (Minneapolis University of Minnesota Press, 1996)
Deconstructive Variations was first published in 1995. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.Unique in its focus and its interdisciplinary reach, Rose Rosengard Subotnik's work is among the most original and challenging being done in American musicology. Her concerns are both formal and sociological, firmly linking music to social and cultural context and breaking down the barriers between music and life.Deconstructive Variations is a sequel to Subotnik's previous collection, Developing Variations. It expands and continues her achievement-the promotion of humanistic criticism as a significant activity in music scholarship and the portrayal of Western art music in relation to the social structures and cultural values of the society that created it.Bringing to her subject a vast range of philosophical, artistic, and historical knowledge, Subotnik applies the insights of Kant, Adorno, Bakhtin, and Derrida to major works of Mozart and Chopin. Each of these essays functions as an argument between two views: for and against the ideal of structural listening; Enlightenment and Romantic readings of The Magic Flute; high-modernist and postmodernist readings of Chopin's A-Major Prelude; and conceptions of reason put forward by Allan Bloom and Spike Lee.
Keywords: Music philosophy and esthetics